Analyzing Urban Parks for Older Adults’ Accessibility in Summer Using Gradient Boosting Decision Trees: A Case Study from Tianjin, China - Haobo Zhao; Gang Feng; Wei Zhao; Yaxin Wang; Fei Chen (Land)
With the acceleration of global aging, outdoor environments, especially urban green space’s planning and design, play a crucial role in not only promoting physical health but also significantly increasing the opportunities for social interactions for older adults. In recent years, the study of age-friendly outdoor environments has attracted increasing attention, with digital methods emerging as essential tools due to their precision and versatility. In this research, three parks in the Nankai District, Tianjin, are taken as the subject of a case study to explore the spatial factors that may exert influence on the behavior distribution of older adults in summery urban parks’ planning and design. With the behavior data of the older adults in the park collected using an Insta360 camera every hour (from 8 a.m. to 15 p.m.), the three parks are divided into a total of 49 areas for further analysis. Additionally, the visual indexes of the spatial syntax are analyzed with Depthmap 10, the sunlight conditions are analyzed with the Tangent model, and some other spatial factors, such as the green space ratio and the hard ground ratio, are calculated according to the semantic segmentation of the 360-degree panoramic view photo from the center of every area. SPSS and Gradient Boosting Decision Trees (GBDTs) are used to reveal not only the correlations between the sunlight conditions and the behavior distribution of behavior of the older adults, but also the importance ranking of spatial factors. Furthermore, some improvement strategies are proposed for spatial facility configuration, park furniture arrangement, rational hardscape planning, as well as greening and landscape design. By exploring how to improve the spatial planning and design of summery urban green space for older adults, this research provides guidance on the creation of urban green spaces in extremely hot weather that are not only visually appealing but also socially equitable and environmentally sustainable.